Revisión bibliográfica de las técnicas y metodologías directas e indirectas para el monitoreo del zorro andino ecuatoriano (lycalopex culpaeus reissii). - Mateus Morales, Deyaneira Betsabe (2023)
In these cases where we do not have multiple studies or projects where the various monitoring techniques have been applied in Lycalopex Culpaeus Reissii requires us to establish a development plan for our project where we establish achievable objectives and these achieve to develop them with existing information directing them to the subject. In addition, we can capture live individuals or remains and excrement of the animal for health status, morphometric measurements and genetic studies, among others. As a species in danger of extinction, neither public nor private organizations have made emphasis on conducting or financing a more congruent research and applying more current techniques and methodologies, innovative, with a much higher percentage of recognizing and knowing about these animals that help us balance the ecosystem where they live. Studies published since 2000 in English and Spanish were included. The analysis of studies published since 2000 was considered appropriate for this review, given that the current evidence of knowledge and evidence may be different from that reported in older studies. In addition, studies in which wild mammalian animals were analyzed were included. Studies in which monitoring of birds, reptiles, amphibians and all species other than terrestrial mammals were analyzed were excluded. The present project will be carried out with a bibliographic review from April to July 2023, it will be based on studies already carried out as thesis, scientific articles, books, among other related investigations where we consider studies applied from the year 2000 to the present 2023, to make a proposal for the monitoring of the Andean Fox in Ecuador. Translated with www.DeepL.com/Translator (free version).With this study we hope to reach all people both in the community and in the country and help many researchers, doctors and future doctors to carry out studies so that they can act in time with the endemic species of each country that neglect them.